PENANAMAN PENDIDIKAN KARAKTER ANAK USIA DINI MELALUI PENERAPAN PROGRAM PARENTING DI TK ALAM BANGKA BELITUNG - Dwi Haryanti; Sisi Milata; Alifia Luqiana Ansory (IJIGAEd: Indonesian Journal of Islamic Golden Age Education, 2021)
Abstract This research is motivated by the importance of parenting programs implemented by parents in school institutions. This is because parents are the primary and first educators for children in the context of the child's personal formation, which is better because children spend a lot of their time at home. The purpose of implementing parenting programs is for parents to get knowledge about how to educate children properly. This study uses qualitative research methods with a descriptive approach. Data collection techniques were carried out using observation, interviews and documentation. The informants in this study consisted of 1 principal, 2 teachers and 5 people involved in the implementation of the parenting program namely parents of students. Data analysis techniques using data display data reduction and conclusion drawing. The results of research on the implementation of the parenting program at Alam Bangka Belitung Kindergarten were carried out in three stages, namely the planning, implementation, and evaluation stages. The planning phase is carried out by holding a meeting, determining the theme and schedule to be held, the implementation phase consists of activities to be carried out and the evaluation phase is carried out by the parenting committee. The benefits of implementing parenting programs in instilling character education in early childhood is that children can develop character in being honest, polite, caring about the environment and having independent character.